Informações e condutas sobre o uso de bebidas alcoólicas entre adolescentes de uma escola pública - Horita, Clarice Maria Aoki (2008)
Use of alcoholic beverages is increasing among adolescents and has been considered of concern of public managers and health and educational professionals due to its deleterious effects. The present study aimed to identify the information and conducts of alcoholic beverages among adolescent students of a public school in the municipality of Guaiçara SP. It was a transversal exploratory and descriptive study conducted along the firs semester of 2008. Main results indicate that 93.9% of the studied adolescents have already experienced alcoholic beverages and that 66.6% had it before the age of 15 years. It is concluded that there is a high percentage of early contact wit alcoholic beverages although the frequency of use was not considered high. The group revealed also a perception that the use of alcoholic beverages is not a positive action.